The Effect of foliar feeding with the organic fertilizer (Huboss) and seaweed extract (Energy Cod) on the set percentage of the “Whashington navel ” orange variety and on some vegetative growth indicators and physical characteristics of its fruits. (Latakia University Journal -Biological Sciences Series, 2024)
The study was carried out during the season (2023) in the Ibn Hani region of Lattakia Governorate, on orange trees of the “Washington Navel” variety,  20 years old, and planted with dimensions of (5 x 5 m). The study aimed to know the effect of foliar spraying with organic fertilizer (Huboss) and seaweed extract (Energy Cod) in the percentage of flowers set (%) and leaf surface area (cm2),  leaves content of total chlorophyll (SPAD), and some physical characteristics of the fruits, The size of the fruits (cm3), and the weight of the fruits (g). The experiment was designed by the completely randomized method; the number of experimental treatments was (9),  and the results were analyzed using the Genstat12 computer  program, Duncan's test was used and the LSR value was calculated at (5%) for field analyzes and (1%) for laboratory analyses to determine Significant differences between the treatments. The study showed, through the results of statistical analysis, the positive effect of foliar spraying with the organic fertilizer (Huboss) and seaweed extract (Energy Cod) in increasing the set percentage of the “Washington navel” variety. The treatment (Huboss 2 cm3/litre + Energy cod 1.5 cm3/litre) was significantly superior to the control (without spraying) and gave the highest average percentage of set flowers (47.23%), while the lowest rate of set  was in the control; It reached (29.40%). the treatment (Huboss 2 cm3/L + Energy cod 1.5 cm3/L); and the treatment (Huboss 2 cm3/litre + Energy cod 1 cm3/litre)  were significantly superior to the rest of the studied treatments in significantly increasing the leaf blade area, the average area of the leaf surface in them was (62.13 cm2) and (57.58 cm2 ), respectively, while the smallest area of the leaf surface was found In the control leaves (25.49 cm2), The results also showed the positive role of foliar spraying with these organic fertilizers in increasing the total chlorophyll content of leaves. All foliar spray treatments, whether mixed or individually, were significantly superior to the control, and The highest percentage of total chlorophyll content in the leaves of the treatment (Huboss 2 cm3/L + Energy cod 1.5 cm3/L) was (68.42 SPAD), while the lowest percentage was in the control leaves and reached (35.71 SPAD). In terms of fruit size and weight, all foliar feeding treatments were significantly superior to the control, and the largest fruit size and weight was in the treatment (Huboss 2 cm3/liter + Energy cod 1.5 cm3/liter); The size of the fruit was (545 cm3), and the average weight of the fruit was (526.9 g). While the lowest average fruit size and weight was in the control (258 g, 267.4 cm3).